Why signal if you are not attractive? Courtship synchrony in a fiddler crab. (6th August 2021) - Harrison, Lauren M; Melo, Gabriela C; Perez, Daniela M; Backwell, Patricia R Y
Abstract: Synchronized male courtship signals are puzzling because males generally compete with each other for females. Male Austruca mjoebergi fiddler crabs wave in synchrony to attract females, but, all else being equal, females have a strong preference for "leader" males that can produce waves before other males ("followers"). So why do followers participate in synchrony? Here, we experimentally investigate three explanations for why followers might wave in synchrony: 1) followers obtain a small proportion of matings, 2) followers are more likely than a leader to attract females if they are positioned closer to her than is the leader, and 3) synchrony functions as a long-distance visual signal that attracts females so there is a net benefit to synchrony for all males. Using robotic male crabs, we found that females show a strong preference for leading males, but followers obtain a "better-than-nothing" proportion of mates. We also showed that closer proximity of a follower to the female did not affect her preference for leaders, although being a leader increased a male's success when he was further from the female than were rival males. Finally, females were more likely to approach a distant group if there was a leader present, suggesting that followers do benefit from participating in synchrony. Abstract : Males that stand out from the crowd attract female attention. Yet male fiddler crabs display in synchrony, even though females prefer "leader" males that wave slightly before the others (followers). So why wave when you are not a leader? Using robotic male crabs, we found that females do prefer leaders over followers, but groups with leaders attract more females from a distance than groups without one. Synchrony can therefore benefit all males within the group.